Infeksi Human Parainfluenza Virus (HPIV) Pada Balita Dengan Infeksi Saluran Pernafasan Akut Berat di RSU Propinsi Nusa Tenggara Barat Tahun 2014 - ekawati, hartanti dian; Puspa, Kartika Dewi; Setiawaty, Vivi; Susilarini, Ni Ketut (Jurnal Biotek Medisiana Indonesia, 2016)
Acute respiratory infection (ARI) is a major cause of morbidity and mortality worldwide, especially in children. An estimated 1.9 million children die because of ARI each year, with 70% of deaths occurred in Africa and Southeast Asia. Human Parainfluenza Virus (HPIV) is the second etiology of ARI in children after Respiratory Syncytial Virus (RSV). This study aims to determine the infection of HPIV in children under 5 years old with ARI at Nusa Tenggara Barat Province Hospital in 2014. Seventy five of 88 archived RNA from children under 5 years old with CT (RNP) number <27 were selected with proportional random sampling. The specimens were tested for HPIV with gel-based RT-PCR using spesific primer for HPIV 1, 2 and 3. Of 75 specimens tested, none is positive for HPIV-2 and only one specimen positive for HPIV-3. This specimen came from 1 year old female from Mataram District. Primer for HPIV-1 failed to optimized, therefore none of the sample is tested with HPIV-1. This finding proved that there was HPIV infection in children under 5 years old with severe cases of ARI at Tenggara Barat Province Hospital in 2014.